2012
DOI: 10.1073/pnas.1117213109
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead transcription factor FoxA1 regulates sweat secretion through Bestrophin 2 anion channel and Na-K-Cl cotransporter 1

Abstract: Body temperature is maintained in a narrow range in mammals, primarily controlled by sweating. In humans, the dynamic thermoregulatory organ, comprised of 2–4 million sweat glands distributed over the body, can secrete up to 4 L of sweat per day, thereby making it possible to withstand high temperatures and endure prolonged physical stress (e.g., long-distance running). The genetic basis for sweat gland function, however, is largely unknown. We find that the forkhead transcription factor, FoxA1, is required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 29 publications
(34 reference statements)
4
79
0
2
Order By: Relevance
“…[7][8][9] Monomers of Best1 oligomerize [10][11][12][13][14] to form a highly conserved homopentameric Ca 2þ -activated ion channel. 8,9 Data from heterologous systems, 15,16 primary human RPE cell culture, 17,18 mouse models, 19,20 the structurally similar paralog bestrophin-2, 21,22 as well as recently published crystal structures 8,9 all unambiguously demonstrate that mammalian Best1 is a calcium-activated anion channel. In addition to functioning as an anion channel, Best1 regulates intracellular Ca 2þ signaling and influences Ca 2þ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Monomers of Best1 oligomerize [10][11][12][13][14] to form a highly conserved homopentameric Ca 2þ -activated ion channel. 8,9 Data from heterologous systems, 15,16 primary human RPE cell culture, 17,18 mouse models, 19,20 the structurally similar paralog bestrophin-2, 21,22 as well as recently published crystal structures 8,9 all unambiguously demonstrate that mammalian Best1 is a calcium-activated anion channel. In addition to functioning as an anion channel, Best1 regulates intracellular Ca 2þ signaling and influences Ca 2þ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Sweat secretion requires coordinated action of sympathetic nerve impulses, regulatory transcription factors and resultant secretory structures assembled during development (Cui et al, 2012;Sato et al, 1989). Sweat gland development includes successive induction, duct formation and secretory region formation (Fig.…”
Section: Discussion the Wnt-eda Cascade In Early Stage Sweat Gland Dementioning
confidence: 99%
“…The other pathway known to be involved in sweat gland maturation, which requires Foxa1, acts at the late stage of development of sweating capacity (Cui et al, 2012). In Shh mutant mice, as in wild type, immunostaining revealed nuclear localization of Foxa1 in scattered developing secretory cells (supplementary material Fig.…”
Section: Involvement Of Bmp and Foxa1 In Auxiliary Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Bestrophin-2 (Best2) is expressed in a number of organs, including the colon, parotid gland, sweat gland, olfactory, and the eye. 11,[14][15][16] In the eye, Best2 is found exclusively in the nonpigmented epithelium (NPE) of the ciliary body (CB). 11,17 We have shown that Best2 functions as a bicarbonate channel.…”
Section: Bestrophinsmentioning
confidence: 99%